PEMANFAATAN KARBON AKTIF ECENG GONDOK (EICHHORNIA CRASSIPES) SEBAGAI MATERIAL ELEKTRODA SUPERKAPASITOR DENGAN VARIASI KOSENTRASI ELEKTROLIT Na2SO4 - Watulingas, Aldo Nandito; Rampengan, Alfrie M.; Tumimomor, Farly Reynol; Wenas, Donny R.; Nusa, Jeilen G. N (SOSCIED, 2024)
The utilization of renewable energy has become a major focus in an effort to reduce dependence on fossil energy sources and reduce negative impacts on the environment, making it important to increase the use of clean and renewable energy. One of the biggest challenges in the application of renewable energy is efficient and sustainable energy storage. In this case, supercapacitors have proven to be a solution as an efficient and sustainable energy storage device. In this study, water hyacinth biomass material was tested as a supercapacitor electrode which was influenced by variations in Na2SO4 electrolyte, namely 1M, 2M, and 3 M, which produced voltages of 1.037 V, 1.404 V, and 1.647 V respectively and electric currents of 18.56 mA, 23.32 mA, and 32.34 mA. From the results of this study, it was found that the sample with an electrolyte concentration of Na2SO4 3 M had higher voltage and amperage values, which amounted to 1.654 V and 32.34 mA due to the greater number of Na+ and SO42- ions in the electrolyte. So it can be concluded that the variation of Na2SO4 electrolyte concentration of 1 M, 2 M, and 3 M results in an increase in the value of voltage and electric current produced by supercapacitors.